New method for extracting microplastics from sediments using a hydrocyclone and sieve - Tetsunori Inoue; Kie Asai; Tomohiro Morisawa; Kazunori Tamaue (Results in Engineering)
Because sediments act as sinks for microplastics, various methods have been developed to extract microplastics from sediments; however, these methods are labor-intensive and expensive, thereby limiting their scalability. In this study, a novel technique involving a hydrocyclone, a type of gravity separator that uses centrifugal force, was developed to rapidly extract microplastics from large volumes of sediment. Sediment samples with varying densities were prepared and spiked with spherical microplastics of different densities and diameters ranging from 1 to 3.175 mm. A hydrocyclone was used to separate fine sediments and microplastics from heavy and coarse particles; subsequently, the separated sediments were sieved to extract the microplastics. The results revealed that the hydrocyclone process efficiently extracted low-density (<1.14 g cm-3) microplastics from approximately 10 kg of fluidized sediment in only 30 s. Such a remarkable processing speed is a significant advantage over existing microplastic extraction methods, which may require various hours to process a smaller amount of sediment. Despite some limitations, the hydrocyclone method has the potential to rapidly extract microplastics from large volumes of sediment without the use of large amounts of toxic and expensive solvents; thus, it may help address microplastic pollution in the marine environment.